Virtual teaching and learning in legal education - Cueva Quispe, Carlos Alberto (2023)
This article aims to evaluate the challenges and opportunities that virtual education offers for university legal education, considering that the virtual educational environment is no longer a mere option, but a necessary tool. For this purpose, in this documentary design research, the general context of virtual education is addressed, to then make a specific approach to the legal education. The author concludes that virtual education tools improve the integral study of Law, and turn challenges -such as the development of critical thinking- into opportunities.